Tourism and Economic Growth in Nepal - Gautam, Bishnu Prasad (NRB Economic Review, 2011)
Tourism has become an important economic activity in all the countries of the world. It creates various direct, indirect and induced effects in the economy. This paper attempts to confirm empirically about the positive impact of tourism in Nepal. It is based on Nepalese data of foreign exchange earnings from tourism and gross domestic product for the period between FY 1974/75 and 2009/10. Co-integration test has been done for ascertaining long run relationship and error correction method for short run dynamics. Granger Causality test has been applied to determine causal relationship between these variables. The evidence confirms the conventional wisdom that of tourism development, that tourism (represented by foreign exchange earnings) causes economic growth both in short and long run. The result also indicates bi-directional causality between these variables.